CAVALLETTI, A. (2019). Vértigo. La tentación de la identidad., traducción de María Teresa D’Meza., Buenos Aires: Adriana Hidalgo editora. - Aponiuk, Juan Cruz (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: CAVALLETTI, A. (2019). Vértigo. La tentación de la identidad., traducción de María Teresa D’Meza., Buenos Aires: Adriana Hidalgo editora.